1991
DOI: 10.1007/bf01789221
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary partial orthotopic liver transplantation (APOLT) for fulminant hepatic failure: First successful case report

Abstract: Fulminant hepatic failure is a life-threatening event with a high mortality rate up to 80%. Orthotopic liver transplantation has markedly decreased this mortality rate and is therefore a well established procedure for hepatic failure. However, this treatment neglects the fact that patients surviving hepatic failure without liver transplantation experienced a complete morphologic and functional recovery of their own liver. Temporary support of liver function in such cases could therefore be desirable and adequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0
5

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(83 citation statements)
references
References 19 publications
0
78
0
5
Order By: Relevance
“…The first successful case of APOLT was reported by Gubernatis et al (2) in 1991 in a 33-year-old woman who had fulminant hepatic failure as a result of viral hepatitis, type A. Histologically, the native liver showed 80% destruction of the hepatic parenchyma followed by its complete restoration approximately 5 months after APOLT. The clinical status of the patient over the period of 16 months after transplantation was excellent, and immunosuppressive therapy was tapered off to surrender immunostain, 100ϫ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The first successful case of APOLT was reported by Gubernatis et al (2) in 1991 in a 33-year-old woman who had fulminant hepatic failure as a result of viral hepatitis, type A. Histologically, the native liver showed 80% destruction of the hepatic parenchyma followed by its complete restoration approximately 5 months after APOLT. The clinical status of the patient over the period of 16 months after transplantation was excellent, and immunosuppressive therapy was tapered off to surrender immunostain, 100ϫ).…”
Section: Discussionmentioning
confidence: 98%
“…Liver cell regeneration after massive hepatic necrosis as a result of fulminant hepatitis has not been pathologically examined in detail because most patients have had a fatal course; even if they had survived, biopsy examination often would have been life threatening because of hemorrhagic diathesis. Recently, however, it has been shown that liver cell regeneration after necrosis can be observed in the native liver after APOLT (2,(5)(6)(7), and there have been a limited number of reports describing regenerative liver cells in fulminant hepatitis in APOLT. In these reports, ductular hepato-cytes were considered to be the putative progenitor cells of hepatocytes (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…[74] These considerations have led to the concept of auxiliary liver transplantation, which doesn't exclude the potential for spontaneous regeneration of the native liver and eventual withdrawal of immunosuppression drugs. [75][76][77][78] In selected patient aged <40 years without hemodynamic instability, the use of ABO compatible, non-steatotic grafts harvested from young donors with normal liver function, can restore normal liver function and prevent the occurrence of irreversible brain damage. After standard immunosuppression, the recovery of the native liver is assessed by biopsies, hepatobiliary scintigraphy and computed tomography.…”
Section: Auxiliary Liver Transplantationmentioning
confidence: 99%
“…The concept of APOLT was introduced by the senior author's group in 1991 to temporarily bridge well-selected patients with potentially reversible acute hepatic failure. 3 Obviously, this technique has been successfully applied in hepatically based metabolic diseases and other indications. As we have come a long way in 200 years from Abernethy to APOLT, we would like to briefly comment on Dr. Emre's interesting article.…”
Section: To the Editorsmentioning
confidence: 99%